Biomphalaria snails and larval trematodes - Toledo, Rafael; Fried, Bernard; SpringerLink (Online service). (New York Springer, 2011)
This book on "Biomphalaria Snails and Larval Trematodes" presents up to date information on the interactions of these snails and their trematode parasites, particularly on Schistosoma spp. larvae. Snails of the genus Biomphalaria are of significant medical importance since several species in this genus are obligate intermediate hosts of the human blood fluke S. mansoni, the causative agent of hepatosplenic schistosomiasis. In addition to the impact of Biomphalaria spp. on public health, these snails are also interesting models for the study of other topics such as population biology, including genetics and demography, proteomics, invertebrate immunobiology, mating systems, biogeography, among others. A purpose of this book is to provide an overview of the recent advances in Biomphalaria spp.-larval trematode interactions, especially in Biomphalaria-schistosome systems. Emphasis is placed on gaps in our knowledge that need to be filled to gain a better understanding of the relationships in these host-parasite systems. This may be critical to obtain a better understanding of our knowledge of the transmission of schistosomiasis and other snail-borne parasitic diseases. The book, ?Biomphalaria Snails and Larval Trematodes? is an ideal volume for researchers and advanced students interested in modern aspects of parasitology , malacology and public health.
Preface -- Biosystematics of Biomphalaria spp. with an Emphasis on Biomphalaria glabrata -- Laboratory Rearing of Biomphalaria glabrata Snails and Maintenance of Larval Schistosomes In Vivo and In Vitro -- Biomphalaria: Natural History, Ecology and Schistosome Transmission -- Studies of Biomphalaria Snails Infected with Larval Trematodes Using Chromatography and Atomic Spectrometry -- Effects of Larval Schistosomes on Biomphalaria snails -- Effects of non-schistosome larval trematodes on Biomphalaria snails -- Immunobiology of Biomphalaria-Trematode Interactions -- Advances in the genomics and proteomics of the freshwater intermediate snail host of Schistosoma mansoni, Biomphalaria glabrata -- The Biological Control of the Snail Hosts of Schistosomes: the Role of Competitor Snails and Biological Invasions -- Index.
Electronic reproduction.
Keywords: Biomphalaria; Biomphalaria -- Parasites; Trematoda -- Larvae; Host-parasite relationships; Schistosomiasis; Snails as carriers of disease; Biomphalaria -- Parasitology; Biomphalaria -- Pathogenicity; Host-parasite interactions; Schistosomiasis -- Transmission; Trematoda -- Pathogenicity; Electronic books